Salmonella serovars trend in poultry Malaysia from 2011 to 2020 - Ibrahim, Muhammad Marwan; Jusoh, Mohammad Bohari; Che Rose, Farid Zamani; Azami, Mohammad Masrin; Roslee, Roseliza (Springer Dordrecht, 2024)
Data and geographical trend of Salmonella serovars infecting poultry in Malaysia is limited. In this study, the trend of Salmonella serovars infection was presented for the past ten years from 2011 to 2020 and the predominant serovars were mapped based on geographical distribution. Analysis of passive surveillance data demonstrated a shift of Salmonella serovars that infected poultry in Malaysia. The Salmonella serovars varied within ten years of registered cases with the Veterinary Research Institute, Ipoh, Malaysia involving samples from live and dead birds. Total number of cases found from the year 2011 to 2020 were 391 cases, involving 73 Salmonella serovars with an additional one group of unclassified serovars known as Salmonella spp. Further analysis revealed that eight serovars were found predominant throughout the ten-year period. These included S. Albany, S. Braenderup, S. Brancaster, S. Corvallis, S. Enteritidis, S. Kentucky, S. Typhimurium and S. Weltevreden. Salmonella spp. (Salmonella that is incapable to be identified based on serotyping) were also one of the major groups observed throughout the years. This study could help the authorities to improvise policies for better disease control programs through the establishment of diagnostic tools for rapid Salmonella screening in poultry.